Active Knowledge Sharing Learning Model Assisted By Mind Mapping Media In Ppkn Competency - Raisita, Ni Made Diah; Asri, I G A Agung Sri; Putra, Made (Universitas Pendidikan Ganesha, 2020)
Learning that is still monotonous causes low student learning activities, especially in PPKn content. This study aims to prove empirically whether there is a significant difference in the knowledge competence of the PPKn group of students who are taught using the Active Knowledge Sharing learning model assisted by Mind Mapping media with groups of students who are taught conventionally in the fourth grade of elementary school. The research method used is a quasi-experimental design or quasi-experimental research with a non-equivalent pre-test post-test control group design. This design cannot fully control the variables from outside that affect the implementation of the experiment. The population in this study was 392 students from all grade 4 students in Gugus IV. The experimental class consisted of 35 students, and the control class totaled 34 students. The sampling method used cluster random sampling, in this technique, the draw is not an individual but a class that has been formed previously without researchers' intervention to create a new class. The data collection used a multiple-choice objective test instrument with one correct answer. The average gain score pre-test and post-test PPKn knowledge competence show the experimental group obtained a result of 0.611 higher than the average competency knowledge of PPKn control class that is 0.474. Hypothesis testing of pre-test and post-test data can be analyzed using the t formula gain score test. The results of tcount = 2.187 and ttable at a significance level of 5% df 67 = 1.996. Therefore tcount> ttable, H0 is rejected and Ha is accepted, meaning that there is a significant difference in the competence of PPKn knowledge between the experimental and the control group. So it can be concluded that there is a significant effect of the Active Knowledge Sharing learning model assisted by Mind Mapping media on the fourth-grade students' PPKn knowledge competency.